PENERAPAN METODE BERCERITA UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN DI RA INSAN TAMAM PAMARAYAN KABUPATEN SERANG PROVINSI BANTEN - Tati Masliati; Elis Mayasri (Jurnal Anak Bangsa, 2023)
This study aims to improve language skills through the storytelling method. This is action research conducted in group B RA Insan Tamam Pamarayan, Serang District, Banten Province. The stages of this action research consist of planning, action implementation, observation and reflection. The subjects of this study were group B students RA Insan Tamam Pamarayan, Serang District, Banten Province who experienced language skills problems. The method used in data collection is a non-test method consisting of survey recordings based on observations and observation photos. The data percentage analysis method used in this study uses an arcieved 80 percent. The results of the analysis of the percentage of rally data by 71% percent are above the achievement indicator. Based on the increase in the percentage, the hypothesis can be accepted. Furthermore, it can be concluded that storytelling can improve language skills in RA Insan Tamam students. The implication of this research is that storytelling can be an alternative to language skills for early childhood students. The application of the storytelling method to language skills in schools is influenced by several factors such as the ability of teachers, school facilities and students. With the synergy of these factors students' language skills will increase optimally